2018
DOI: 10.1117/1.jbo.23.10.105001
|View full text |Cite
|
Sign up to set email alerts
|

Nonscanning large-area Raman imaging for ex vivo/in vivo skin cancer discrimination

Abstract: Nonscanning large-area Raman imaging for ex vivo/in vivo skin cancer discrimination,"Abstract. Imaging Raman spectroscopy can be used to identify cancerous tissue. Traditionally, a step-by-step scanning of the sample is applied to generate a Raman image, which, however, is too slow for the routine examination of patients. By transferring the technique of integral field spectroscopy (IFS) from astronomy to Raman imaging, it became possible to record entire Raman images quickly within one single exposure without… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
12
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 43 publications
0
12
0
Order By: Relevance
“…The fluorescence, introduced by the high lipofuscin content could possibly be avoided when a longer wavelength illumination source for Raman spectroscopy is chosen. 76 The relatively long acquisition time of spontaneous Raman scattering when measuring a large area could be overcome either by non-scanning Raman techniques 77 or by stimulated Raman scattering (SRS) imaging. 18…”
Section: Resultsmentioning
confidence: 99%
“…The fluorescence, introduced by the high lipofuscin content could possibly be avoided when a longer wavelength illumination source for Raman spectroscopy is chosen. 76 The relatively long acquisition time of spontaneous Raman scattering when measuring a large area could be overcome either by non-scanning Raman techniques 77 or by stimulated Raman scattering (SRS) imaging. 18…”
Section: Resultsmentioning
confidence: 99%
“…Optical biopsy based on RS and AF application demonstrates a high level of accuracy (exceeding 90%) in the diagnosis of skin cancer . Moreover, Schmälzlin et al offered application of the Raman imaging system to study cancer biopsy samples . Many research teams have been trying to increase the efficiency of diagnostics by using more sensitive and expensive equipment (high spectral resolution, deeply cooled detectors, etc.).…”
Section: Introductionmentioning
confidence: 99%
“…38 However, there remains a lack of Raman imaging systems with large FOV for in vivo human clinical use. The only Raman imaging system with a large measurement area (1 cm 2 ) that was developed and tested for a human in vivo application is reported by Schmälzlin et al (2018) 35 for skin cancer although no cancer margin detection was demonstrated.…”
Section: Introductionmentioning
confidence: 99%